Wabanaki Forest Lands in Maine: An Evolving Story - Irland, Lloyd (Maine Policy Review, 2025)
The Wabanaki Nations’ homelands have been whittled down to a tiny fraction of their original size. Only one tract, Indian Township (Motahkomikuk) in eastern Maine, has been in continuous tribal ownership since before statehood in 1820. Much Wabanaki forest land was in industrial ownership and managed for timber as recently as 30–40 years ago. This article sets forestry issues into the context of larger debates over tribal sovereignty and provides a short historical introduction and overview of the forest management issues. The timing is significant because of the release of the Indian Forest Management Assessment Team IV report and a new Secretary of Interior who will pursue priorities different from his predecessor.